Index System and Evaluation Method of Geological Environment Suitability for Human Health - Xingchun JIAO; Zhaohe ZHANG; Wei FANG; Ruimin LI; Jiuchen LIU; Wenbin JIA (Yankuang ceshi)
BACKGROUNDHuman health is closely related to the geological environment. There’re various geological environment factors affecting human health in a composite way. Geological background characteristics, including tectonic structure, lithologic features, and landform configuration shape the living conditions of human being. Climate conditions and the spatial and temporal variation characteristics influence the comfortable level for habitation. More importantly, the direct and indirect impacts of elements and chemicals in rock, soil, water, and air and biosphere on human health are comprehensive and significant. In addition, various human activities have increasingly influenced geological substances and geological processes since the Industrial Revolution, which together with natural geological factors contribute to the unique public health characteristics of a region. (Fig.1). Quantifying the impact of geological environment on human health has always been a hot topic in the study of environment, geology, and other disciplines. In terms of environmental health impact assessment, many scholars or organizations have developed different evaluation indicator systems from different research perspectives. Existing studies focus on assessing health risks from a single perspective, such as chemical substances or engineering construction, while comprehensive evaluation of the health impact of the geological environment from the perspective of the earth system is still rare. In today’s world of rapid socio-economic development, the relationship between human health and geological environment is even more complex, and single methods of evaluating environmental and population health are increasingly inadequate to cope with the increasingly complex health factors. The study of the suitability of geological environment for human health is rapidly progressing under a new theoretical framework.RESULTS(1) The evaluation index system. A comprehensive geological environmental health suitability evaluation index system was developed based on a composite perspective, taking into account multiple dimensions such as environmental geochemistry, regional geological background, climate conditions, and intensity of human activities. The rock strata, topography, climate conditions, as well as the geochemical quality of multiple media such as soil, water, and crops in a certain area, shape the specific lifestyle and behavioral habits of the regional population, resulting in unique regional health characteristics.　　(2) GHI evaluation method. The geological health index (GHI) evaluation method was established, which divides the health suitability of regional geological environments into five grades based on GHI scores: excellent (85 points or above), good (75-85), fair (60-75), poor (50-60), and very poor, representing the conditions of extremely suitable, suitable, moderately suitable, possibly suitable, and unsuitable for human health.　　(3) Case study. A case study was conducted in Anji and Longyou counties of Zhejiang Province using the GHI method. The overall GHI scores of the two regions indicated that the health suitability of the geological environment in Anji county was rated as “good” (78.16), while Longyou county was rated as “excellent” (85.50). The evaluation results reflected the health suitability of the regional geological environment, and could provide guidance for rational utilization of geological resources beneficial to health and avoidance of geological risks adverse to health.DISCUSSION(1) Principles for choosing indicators. The assessment index system was established following scientific principles, making sure the indicators are representative for general geological environment and closely related to human health. The influence of each indicator on health should be based on evidence, which can objectively reflect the difference of geological environment on population health. Furthermore, the indicators should be available in most settings and be simple to calculate. It is beneficial to have the current environmental industry or health industry standards as a reference.　　(2) Composition of the index system. The GHI index system included 15 specific indicators, which were listed in Table 1. Four sub-indexes were classified to represent the influencing factors of geological environment on human health, which were climate, geological background, environmental geochemistry characteristics and human activities. Two indicators of human comfort level, representing integrated influence of air temperature, humidity and wind, and incidence of extreme weather, were used to characterize the climate factors that affect human health. Four indicators, including regional crustal stability, natural environmental radioactivity, altitude and vegetation coverage, which were closely related to population health, were extracted to characterize the suitability of spatial characteristics of structure, rock, strata and epigenetic systems to population health. Seven indicators including environmental air quality, drinking water quality, irrigation water quality, cultivated land soil quality, agricultural product quality, water resource quantity and land resource quantity were used to characterize the environmental geochemical elements that have an important impact on population health. Human activities have influenced and changed the natural substances at global and regional scales, which have brought about significant impacts on the survival of organisms and human health. In this study, population density and per capita gross industrial and agricultural product were used to characterize the intensity of human activities.　　(3) GHI evaluation method. The evaluation of the health suitability of the geological environment was performed following the processes of data standardization, weight assignment, index score calculation and evaluation level classification. A two-step method was proposed to standardize data processing to complete the evaluation process of health suitability of the geological environment. Firstly, the environmental quality level corresponding to all indicators was determined by comparing with the national average level, national and industrial standards and specifications. Secondly, the impact of different levels of geological environmental quality on population health was evaluated with reference to literature, world and national health standards, and the degree of impact is measured with 0-100 points. The weights were assigned to each indicator according to analytic hierarchy procedure (AHP). The scores of each sub-index and total GHI index were calculated according to corresponding equation. Finally, the health suitability of regional geological environment is divided into five levels: excellent (85 points and above), good (75-85), general (60-75), poor (50-60) and bad (below 50), which respectively represent the state of extremely suitable, suitable, relatively suitable, possibly suitable and unsuitable to population health in certain regional geological environment.　　(4) Case study. A case study was conducted in Anji and Longyou counties of Zhejiang Province using the GHI method. The results showed that the two regions scored similarly in the three sub-indices of “climate conditions”, “geological background”, and “human activity intensity”, while there was a significant difference in the sub-index of “environmental geochemistry”. This was because the agricultural products in the selenium-enriched area of Anji were severely contaminated with heavy metals, while there was no such phenomenon in the selenium-enriched land of Longyou County. The overall GHI scores of the two regions indicated that the health suitability of the geological environment in Anji county was rated as “good” (78.16), while Longyou County was rated as “excellent” (85.50). However, the investigation found little difference in the health status of the residents in the two areas, with the average life expectancy of the residents in both areas higher than the national average. This suggests that although the geological environment in Anji County has high geochemical characteristics of Cd and Ni, the selenium-enriched environment has played a certain compensatory role, and Anji County still maintains an overall level of “suitable” for human health.　　(5) Limitations and future research prospects. With the rapid development of global society and economy, the relationship between population health and geological environment is complicated, and the evaluation method with single dimension is difficult to adapt to the increasingly complicated situation of health influencing factors. In this study, the GHI method is proposed to evaluate the health suitability of geological environment. Based on the multi-dimension of environmental geochemistry, regional geological background, climate condition and human activity intensity, the evaluation index system and evaluation method of geological environmental health suitability are studied from a composite perspective. The GHI evaluation method could be used for regional geological environment evaluation and zoning, and the evaluation results could help manage a more habitable environment and improve the health level of the population. However, there are still some limitations to this approach: ①There is no grouping of the target population. ②The exposure time is not considered. ③The actual intake of water and food is not confirmed. To sum up, the method will be continuously improved by refining the index system, to develop a health suitability assessment method with greater spatial heterogeneity that could meet the needs of the public and government to the greatest extent.